A “Standing” Amendment to the Federal Rules of Civil Procedure - Daniel O. Bernstine (Washington University Law Quarterly, 1979)
This Article examines the constitutional and prudential policies underlying the standing requirement, and concludes that a federal court may render a valid judgment when the defendant fails to raise the standing issue prior to judgment.
Keywords: Standing to sue; Federal Rules of Civil Procedure